Gestational diabetes mellitus (GDM): risk factors and impact on neonatal outcome of an indigenous South Asian cohort - Gunawardane, P.T.K.; Wijeyaratne, C.N.; Arandara, D.C.; Arasalingam, A.; Dodampahala, S.H.; Seneviratne, H.R. (The Sri Lanka College of Obstetricians and Gynaecologists, 2006)
OBJECTIVE: To assess risk factors and pregnancy outcomes of GDM in Sri Lankans. DESIGN: Case-control study SETTING: Department of Obstetrics & Gynaecology, Faculty of Medicine University of Colombo, Sri Lanka. SAMPLE: 274 indigenous Sri Lankans with previous GDM and 168 ethnically matched controls. METHODS: Post partum review of hospital case records and by patient interview, of risk factors and outcome of index pregnancy managed in a single unit (ACOG guidelines, 2001). RESULTS (GDM VS. CONTROLS): Risk factors - Mean age 33.4ñ0.6 vs. 32.3ñ0.8 years. 78 percent GDM para2 or > with 33.7 percent having 2 or > children vs. 74 percent controls para 2 or > with 60 percent having 2 or > children (p = 0.001). Significant risks included maternal age >35 years (OR=1.8, 95 percent CI=1.1-2.8, p=0.008), previous stillbirth with fetal macrosomia (OR=3.55,95 percent CI= 1.6-8.2, p=0.005), family history of diabetes (OR=4.5, 95 percent CI=1.6-6.9, p=0.004), and high maternal BMI at antenatal booking (OR=16.8, 95 percent CI= 9.6-26.9, p=0.00001). 39 (14.2 percent) in GDM group had previous GDM. OUTCOME OF INDEX PREGNANCY MANAGED FOR GDM VS. CONTROLS: Mean period of gestation at delivery 3 8.1 ñ1.9 vs. 38.2ñ2.05 weeks, p>0.05.Pre-term delivery 34(12.4 percent) vs. 19(5.3 percent), p=0.01. Vaginal delivery 110(40.1 percent) vs. 95(56.5 percent), p=0.08, Caesarean delivery 164(59.8 percent) vs. 73(43.4 percent), p= 0.01. Live births 270(98.5 percent) vs. 168(100 percent), p=0.1, stillbirth 4(1.5 percent) vs. 0, p=0.001. Mean birth weight (BW) 3.01ñ0.56 vs. 3.03ñ0.54kg, p=0.08; Low BW 42(15.3 percent) vs. 19(11.3 percent), p=0.1 and BW >3.5kg (2SDS) 42(15.3 percent) vs. 16(9.5 percent), p=0.1. CONCLUSIONS: Sri Lankan women have similar risks for developing GDM as reported in other ethnic groups, with maternal obesity a leading contributor. This data confirms early detection and effective control of gestational diabetes leads to significant reduction of perinatal morbidity and mortality.
Keywords: GDM; ASIAN